2015
DOI: 10.1186/s12889-015-2687-0
|View full text |Cite
|
Sign up to set email alerts
|

Space, body, time and relationship experiences of recess physical activity: a qualitative case study among the least physical active schoolchildren

Abstract: BackgroundIncreasing recess physical activity has been the aim of several interventions, as this setting can provide numerous physical activity opportunities. However, it is unclear if these interventions are equally effective for all children, or if they only appeal to children who are already physically active. This study was conducted to explore the least physically active children’s “lived experiences” within four existential lifeworlds linked to physical activity during recess: space, body, time, and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 73 publications
1
31
1
2
Order By: Relevance
“…Similarly, a qualitative study of lived experiences set within an intervention aiming to increase PA during recess, concluded that the least active children increased recess PA through the inclusion of teacher-led play, but not free play [39]. Generally, boys’ motivation for engaging in PA is intrinsic and girls’ to a larger extent driven by both intrinsic and extrinsic motivation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a qualitative study of lived experiences set within an intervention aiming to increase PA during recess, concluded that the least active children increased recess PA through the inclusion of teacher-led play, but not free play [39]. Generally, boys’ motivation for engaging in PA is intrinsic and girls’ to a larger extent driven by both intrinsic and extrinsic motivation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results demonstrated that complaints start at levels below the WHO guidelines for these parameters. Prior research in the Eastern Region suggests that groundwater sources are underutilized in part due to these WQ problems (Kosinski et al, 2016; Kulinkina et al, 2016). Undesirable organoleptic characteristics of groundwater from BHs are also likely linked to consumption of microbiologically and chemically contaminated surface water (Kulinkina et al, 2017), which can lead to substantial detrimental public health impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Atiwa District also has a high rate of improved water access in terms of the number of water sources per population (Kulinkina et al, 2017), potentially as a result of having to drill more BHs to find acceptable water quality. Despite this, surface water is highly preferred and extensively used in some communities (Kosinski et al, 2016), a particularly unsafe practice in the presence of gold mining activities. While the extremely high turbidity levels from several years of mining pollution have rendered the Birim River unusable, mining activities are beginning to affect many of its tributaries that are still used for drinking, cooking, and laundry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four hundred and forty-seven participants were initially recruited at two years of age through childcare centers, the County Health Department, and the local Women, Infants, and Children program. Additional details about sample recruitment and the adolescent health assessments may be found elsewhere (43, 44). The recruitment sample was diverse; 62.9% of the children were European American, 32.4% African American, 3.3% biracial, and 1.4% of other race/ethnicity.…”
Section: Methodsmentioning
confidence: 99%